COMPARISON OF BUSINESS COMPETITION INSTITUTIONS BETWEEN INDONESIA AND THAILAND AS A FORM OF STRENGTHENING THE INDONESIAN BUSINESS COMPETITION SUPERVISORY - Fibrianti, Nurul; Wahanisa, Rofi (IBLAM LAW REVIEW, 2023)
Competition is a necessity in the business world, business actors are no stranger to competition between business actors in carrying out their business activities. This is done solely for profit. The state established the Business Competition Supervisory Commission (KPPU) as a form of the state's presence in protecting business actors who have acted honestly in carrying out their business activities. This research aims to identify problems related to the duties and authorities of the Commission for the Supervision of Business Competition in Indonesia and Thailand to then carry out a comparative study. The method used by researchers is a normative juridical approach. According to Soerjono Soekanto, the normative juridical approach is legal research conducted by examining literature or secondary data as the basis for research by conducting a search of regulations and literature related to the problem under study.